Prevalence of Cesarean section and its related factors - maryam khsravi; moohamadreza armat; nahid jarolahi (Guilan University of Medical Sciences, 2006)
Introduction: According to WHO, no region in the world can justify a Cesarean rate higher ‎than ‎‏10‏‎-‎‏15 ‏percent. But unfortunately, Published statistics for most areas all‏ ‏over the world ‎show a great difference with this ratio. Cesarean births pose greater risk to the mothers ‎health, slow maternal recovery and increase relative mortality rate. ‎ Objective: This study has been performed to determine the rate and related factors for ‎Cesarean birth in Bojnurd.‎ Methods: This is a descriptive – analytic study and its samples consists of ‎‏473‏‎ mothers who ‎gave birth to term, single Infants with birth weight & higher than ‎‏2500 ‏gram‏.‏‎ Type of delivery ‎as independent variable and twenty other variables mainly relation to family socio-economic ‎status and mother and infant characteristics as dependent variables were studied. Data needed ‎was collected through direct observation and interview with mothers.‎ Results: The percentage of CS in Bojnurd was‏ ‏‎(‎‏25.4%‏‎) and rate of CS in cases such as ‎better job and higher parental education (P<‎‏0.006‏‎), residency in city (P=‎‏0.001‏‎), less ‎family numbers (P=‎‏0.008‏‎), birth weight of ‎‏3900‏‎ g or more (P=‎‏0.055‏‎), larger head ‎circumference (P=‎‏0.01‏‎), increased weight of mother near delivery (P=‎‏0.13‏‎) and higher age ‎of mother (P=‎‏0.054‏‎) were significantly increased.‎ Conclusion: Independent variables related to family Socio-economic status and also variables ‎related to mother and infant such as mother age and weight near delivery which effects head ‎circumference and birth weight had the most influencing on top of delivery. Rate of CS in ‎mothers with better socio-economic conditions and also older mothers was significantly ‎higher. Therefore, it seems that giving information to families and plans to lesser the age of ‎marriage can decrease the rate of unnecessary, expensive and dangerous CS.‎